Degradasi Norma â€œStrict Liabilityâ€ Dalam Penegakan Hukum Lingkungan - Abdul Rokhim (Fakultas Hukum Universitas Islam Malang, 2022)
Law enforcement on cases of environmental pollution and/or destruction is very difficult to implement in Indonesia. One of the contributing factors is the normalization of the principle of strict liability which is not firm and has a limited scope. This study aims to analyze legal issues regarding the normalization of the principle of strict liability in UUPPLH and its application in law enforcement in cases of pollution and/or environmental destruction. This research uses normative juridical research. The results show that the UUCK has deviated from the main characteristics of the strict liability doctrine, so the strict liability principle becomes meaningless and its purpose is degraded. Therefore, victims of environmental pollution and/or destruction are required to prove the element of guilt of the perpetrator when filing a lawsuit based on the strict liability principle from the UUCK in perspective.